2012
DOI: 10.1073/pnas.1114944109
|View full text |Cite
|
Sign up to set email alerts
|

Transport of drugs by the multidrug transporter AcrB involves an access and a deep binding pocket that are separated by a switch-loop

Abstract: AcrAB-TolC is the major efflux protein complex in Escherichia coli extruding a vast variety of antimicrobial agents from the cell. The inner membrane component AcrB is a homotrimer, and it has been postulated that the monomers cycle consecutively through three conformational stages designated loose (L), tight (T), and open (O) in a concerted fashion. Binding of drugs has been shown at a periplasmic deep binding pocket in the T conformation. The initial drug-binding step and transport to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
588
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(622 citation statements)
references
References 43 publications
30
588
2
2
Order By: Relevance
“…Recent studies on the crystal structure of substrate bound AcrB (28)(29)(30) and biochemical mapping of the substrate path (31,32) have shown that there are multiple drug-binding sites in the large periplasmic domain of AcrB. We propose that AcrZ binding to AcrB could trigger conformational changes in the periplasmic domain, thus directly affecting the recognition and capture of certain substrates, such as substrates with lower hydrophobicity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the crystal structure of substrate bound AcrB (28)(29)(30) and biochemical mapping of the substrate path (31,32) have shown that there are multiple drug-binding sites in the large periplasmic domain of AcrB. We propose that AcrZ binding to AcrB could trigger conformational changes in the periplasmic domain, thus directly affecting the recognition and capture of certain substrates, such as substrates with lower hydrophobicity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1). This in turn could affect the affinity to various drugs such as doxorubicin and minocycline whose binding positions have been identified by cocrystallization experiments (22) (Fig. 1).…”
Section: Computational Structural Biology Suggests That Drug Specificmentioning
confidence: 99%
“…In the available crystal structures of AcrB in its apo-(PDB ID code 2J8S) (24) and in doxorubicin-(PDB ID code 4DX7) and minocycline-bound forms (PDB ID code 4DX5) (22), G288 is located in the middle of a beta strand, with the neighboring side chains pointing away from the pocket, suggesting that the substituted side chain will protrude into the pocket cavity. Hence, this bulky and charged aspartate residue will have a drastic impact on structure and Experiments were carried out on at least three separate occasions and the mode value is presented.…”
Section: Computational Structural Biology Suggests That Drug Specificmentioning
confidence: 99%
See 1 more Smart Citation
“…5). A number of efflux pump inhibitors phenylalanine-arginine β-naphthylamide (PAβN) [26][27], 1-1-Naphthylmethyl-piperazine (NMP), pyridopyrimidine one and pyrazolopyridines) exerted their inhibitory activity against bacterial efflux pump at concentration range from 70 µg/ml [28] to 100 µg/ml [29], for example, PAβN registered half maximum activity approximately at 70 µg/ml whereas NMP caused EtBr accumulation at 100 µg/ml. An EPI (such as NMP) can also act as antibacterial agent at four-fold (400 µg/ml) concentration to its normal EPI concentration.…”
Section: Typhi Over-expressing Efflux Pumps As Indicated By Etbr Carmentioning
confidence: 99%